Penerapan Teori Difusi Inovasi pada Pembaruan Website Kecamatan Tanjung Raya untuk Membangun Platform Smart dan Partisipatif - Zahra Aqilah Dytihana; Yetty Sembiring; Rozali Ilham; Fitri Yul Dewi Marta (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
This research explores the application of Everett Rogers' Diffusion of Innovations Theory in updating the Tanjung Raya Sub-district website to build an excellent and participatory platform. A website that is not updated generates various problems, such as inaccurate information, low community participation, and compromised service efficiency. Through analyzing the current state of the website and implementing excellent features such as e-services, community forums, real-time updates, and social media integration, this research signifies that updating the website can improve the quality of public services and community engagement. A cost-benefit analysis with a ratio of 3.89 shows that every Rp1 invested yields an economic benefit of Rp3.89, confirming the effectiveness of this investment. The results suggest that up-to-date and participatory government websites are essential in supporting government transparency and accountability. Further research is recommended to explore the long-term impact of website updates on public participation and efficiency of public services, as well as effective communication strategies to initiate digital innovations in government.